A nipple‐valve technique for ureteroneocystostomy in pediatric kidney transplantation. (17th November 2014) - Van Arendonk, Kyle J.; Goldstein, Seth D.; Salazar, Jose H.; Kumar, Komal; Lau, Henry T.; Colombani, Paul M.
Abstract The ureteroneocystostomy in kidney transplantation can be performed with a variety of techniques. Over a 20‐yr period, we utilized a technique of nipple‐valve ureteroneocystostomy for the pediatric kidney transplants performed at our institution. The distal ureter is everted upon itself and anchored in place with four interrupted sutures to create a nipple valve, which is then inserted into the bladder and sewn mucosa‐to‐mucosa with the same sutures. The muscularis layer is closed around the ureter without tunneling and without routine ureteral stenting. After 109 transplants, patient survival was 97.2, 97.2, and 86.9% at one, five, and 10 yr, respectively. Graft survival was 91.7, 71.7, and 53.9% at one, five, and 10 yr, respectively. The most common cause of graft loss was acute or chronic rejection, seen in 75% of those experiencing graft loss. Two patients (1.8%) developed pyelonephritis in the transplanted kidney. Nipple‐valve ureteroneocystostomy in pediatric kidney transplantation is a safe and simple method for performing the ureterovesical anastomosis with a low rate of pyelonephritis after transplantation.